Conceptualizing Lennox–Gastaut Syndrome as a Secondary Network Epilepsy - Archer, John S.; Warren, Aaron E. L.; Jackson, Graeme D.; Abbott, David F. (Frontiers in Neurology, 2014)
Lennox-Gastaut Syndrome (LGS) is a category of severe, disabling epilepsy, characterised by frequent, treatment-resistant seizures and cognitive impairment. EEG (electroencephalography) shows characteristic generalised epileptic activity that is similar in those with lesional, genetic or unknown causes, suggesting a common underlying mechanism. The condition typically begins in young children, leaving many severely disabled with recurring seizures throughout their adult life. Scalp EEG of the tonic seizures of LGS is characterised by a diffuse high voltage slow transient evolving into generalised low voltage fast activity, likely reflecting sustained fast neuronal firing over a wide cortical area. The typical interictal discharges (runs of slow spike-and-wave (SSW) and bursts of generalised paroxysmal fast activity (GPFA)) also have a ‘generalised’ electrical field, suggesting widespread cortical involvement. Recent brain mapping studies have begun to reveal which cortical and subcortical regions are active during these ‘generalised’ discharges. In this critical review we examine findings from neuroimaging studies of LGS and place these in the context of the electrical and clinical features of the syndrome. We suggest that LGS can be conceptualised as a ‘secondary network epilepsy’, where the epileptic activity is expressed through large-scale brain networks, particularly the attention and default-mode networks. Cortical lesions, when present, appear to chronically interact with these networks to produce network instability rather than triggering each individual epileptic discharge. LGS can be considered a ‘secondary’ network epilepsy because the epileptic manifestations of the disorder reflect the networks being driven, rather than the specific initiating process.